State-of-charge estimation for lead–acid batteries via embeddings and observers. (April 2019) - Carnevale, D.; Possieri, C.; Sassano, M.
Abstract: In this paper, an approach is proposed to estimate the open-circuit voltage of a battery – and consequently the battery State-of-Charge during normal operation of electric vehicles – by only measuring the charge/discharge current and the voltage on the load. The result is achieved, without any knowledge of the characteristic values of the battery model, by combining a system embedding with a high-gain observer design strategy. Interestingly, the method is based on genuinely nonlinear estimation strategies, hence it does not suffer the typical drawbacks of linear approaches, including the requirement for persistence of excitation of the charge/discharge current.